2015
DOI: 10.1242/bio.013672
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial topography for repetitive tooth formation

Abstract: During the formation of repetitive ectodermally derived organs such as mammary glands, lateral line and teeth, the tissue primordium iteratively initiates new structures. In the case of successional molar development, new teeth appear sequentially in the posterior region of the jaw from Sox2+ cells in association with the posterior aspect of a pre-existing tooth. The sequence of molar development is well known, however, the epithelial topography involved in the formation of a new tooth is unclear. Here, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…The interdental lamina does not produce teeth, in contrast to the tooth-producing successional dental lamina located adjacent to the first generation teeth. Sox2 and Sox9 have recently been shown to have complementary patterns of expression in the growing molar tail, which will form the serially added molars at the back of the mouth (Gaete et al, 2015). We therefore analysed the expression of these two progenitor markers in the two parts of the minipig dental lamina, and compared their expression with that in the RSDL in the mouse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interdental lamina does not produce teeth, in contrast to the tooth-producing successional dental lamina located adjacent to the first generation teeth. Sox2 and Sox9 have recently been shown to have complementary patterns of expression in the growing molar tail, which will form the serially added molars at the back of the mouth (Gaete et al, 2015). We therefore analysed the expression of these two progenitor markers in the two parts of the minipig dental lamina, and compared their expression with that in the RSDL in the mouse.…”
Section: Resultsmentioning
confidence: 99%
“…The Bmp4 probe was a gift from Prof. Karen Lyons (University of California at Los Angeles, USA; Lyons et al, 1990); the ectodin probe (Wise) was a gift from Dr Atsushi Ohazama (King's College London, UK;Ohazama et al, 2008); Fgf3 and Fgf4 probes were gifts from Prof. Ivor Mason (King's College London, UK; Mahmood et al, 1996); the Pax9 probe was a gift from Dr Heiko Peters (Newcastle University, UK; Peters et al, 1998); and the Shh probe was a gift from Prof. Andy McMahon (University of Southern California, Los Angeles, USA; Bitgood and McMahon, 1995). In situ hybridisation of craniofacial sections was carried out as previously described by Gaete et al (2015).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…We therefore used ex vivo organ cultures to examine the effect of increased Wnt/ β-catenin signaling on the formation of M2 in control mice. M2 develops from the posterior extension of the M1 epithelium, also referred to as posterior dental lamina, posterior tail (tip) and continual lamina (Juuri et al, 2013;Gaete et al, 2015;Juuri and Balic, 2017). We dissected mouse embryonic M1 tooth germs at the stage when M2 is initiated (E14.5) and the continual lamina, which indicates the starting point of M2 development, is clearly visible (Fig.…”
Section: Stimulation Of Wnt/β-catenin Signaling In Embryonic Molars Bmentioning
confidence: 99%
“…Additionally, SOX2 expression, which is a marker of DESCs in M1 [3] , is associated with sequential development directed to the posterior position [1] . Marcia Gaete et al reported that epithelium of the anterior-molar tail could grow by the posterior movement of epithelial cells, followed by infolding and stratification involving a population of SOX2 + /SOX9 + cells [4] .…”
Section: Introductionmentioning
confidence: 99%